Differences in results of infrabony pocket treatment with addition of platelet rich fibrin and platelet rich plasma gel in DFDBA bone graft - Netta Anggraini; Sri Pramestri Lastianny; Al Sri Koes Soesilowati (Faculty of Dentistry, Universitas Gadjah Mada, 2019)
Treatment of infrabony pocket makes use of bone graft material demineralized freeze dried bone allograft (DFDBA) from different individuals which has undergone demineralization process and it is osteoinductive. Enhancement of growth factor was done by adding platelet rich fibrin (PRF) and platelet rich plasma (PRP). PRP is activated with an addition of calcium chloride CaCl2) to form gel. The method used to apply the bone grafting material is open flap debridement OFD). This research aimed to reveal the differences in the results of infrabony pocket treatment using PRF and PRP gel with an addition of DFDBA. The sample was taken from 20 infrabony pocket points divided into 2 groups, 10 infrabony pocket were treated with OFD+DFDBA+PRF and the other were treated with OFD+DFDBA+PRP gel. Pocket depth (PD) was measured on the baseline and the first and third month after treatment. Alveolar bone height was measured using cone beam computed tomography (CBCT) radiograph on the baseline to the third month after treatment. The results of this research showed that there was difference in the results of infrabony pocket treatment using PRF and PRP gel with an addition of DFDBA which could be observed from a reduction in PD from the baseline, month 1 and month 3 as well as reduction in alveolar bone height from the baseline to month 3. This research concluded that infrabony pocket treatment PRF application yields better results than PRP gel application in terms of PD and alveolar bone height reduction.